Karakter Lumpur Pemboran Berbahan Dasar Bentonite Lokal Tulungagung dan Boyolali Mengacu Standar API 13A dengan Variasi Additive Polyamine - Ilcham, Adi; Gardatoga, Obed Rama; Irma, Ade (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
This study examined the feasibility of using locally sourced bentonite as drilling mud, with the aim of reducing the cost of imported drilling mud. Bentonite, a soil type containing a high concentration of smectite or montmorillonite, is widely used in drilling mud. The physical properties of drilling mud made from bentonite from Boyolali and Tulungagung were compared, with the addition of various additives to meet the API 13A standard. The research found that drilling mud made from Boyolali bentonite showed physical properties that were closer to the API 13A standard compared to Tulungagung bentonite. Specifically, adding 7 grams (12%) of polyamine to Boyolali bentonite mud produced a volume of filtrate loss and mud cake thickness closest to the API 13A standard, namely 10.8 ml (maximum 15 ml) and 0.14 cm (maximum 0.28 cm), respectively. Adding 2.3 grams (5.04%) of KOH resulted in the highest pH value of 13, while adding 2.5 grams (1.17%) of Na2CO3 produced the least amount of filtrate loss, namely 7.2 ml (maximum 15 ml), with a mud cake thickness of 0.27 cm (maximum 0.28 cm)